A New Era of Consumer Behavior In and Beyond the Pandemic - Ayman, Umut (Business, Management and Economics, 2023)
The complexities of consumer behavior call for comprehensive and detailed analytical studies. The need for both businesses and academics across the world to understand the behavior of consumers in crisis situations has been clearly illustrated by the Covid pandemic. A New Era of Consumer Behavior - In and Beyond the Pandemic presents research on both theoretical and practical aspects of this topic in three sections: "Digital Shifts in Consumer Behavior", "Digitalization of Consumer Behavior in the Tourism Sector" and "Consumer Protection and Sustainability".